ChemInform Abstract: A Bioinspired Route to Indanes and Cyclopentannulated Hetarenes via (3 + 2)‐Cyclodimerization of Donor—Acceptor Cyclopropanes. Issue 15 (15th April 2014) - Ivanova, Olga A.; Budynina, Ekaterina M.; Skvortsov, Dmitriy A.; Limoge, Michelle; Bakin, Andrei V.; Chagarovskiy, Alexey O.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract The Lewis‐acid catalyzed reaction gives the title compounds stereoselectively in short time and high yields.